FRI0488 Ultrasound detects joint damage and bleeding in haemophilic arthropathy: the utility of a score. (23rd January 2014) - Melchiorre, D.; Linari, S.; Morfini, M.; Matucci-Cerinic, M.
Abstract : Background: Haemarthrosis is the trigger of haemophilic arthropathy (HA), because bleeding starts soon synovitis, damages cartilage, and leads to loss of function and disability. Objectives: To investigate the capacity of ultrasonography (US) to detect bleeding and joint damage in HA. Methods: The joints of 82 patients (pts) with Haemophilia A or B were consecutively evaluated and scored (score ranging from 0 to 21) for effusion (E), bone remodelling (BR), cartilage damage (CD), synovial hypertrophy (SH), haemosiderin (H), osteophytes (O), haemarthrosis (Hae), erosion (Er) and fibrotic septa (FS) with US. X-rays [Pettersson Score (PXS)] were performed in 81 pts and clinical evaluation [World Federation Haemophiliac orthopaedic score (WFHO)] was done in all pts. Power Doppler US (PDUS) was performed in all patients on the knee, ankle and elbow joints. Results: A total of 103 joints were studied (60 knees; 22 elbows and 21 ankles). US showed effusion in 77 joint, bone remodelling in 82, cartilage damage in 74, synovial hypertrophy in 65, haemosiderin in 49, osteophytes in 46, haemarthrosis in 34, erosion in 25 and fibrotic septa in 12. In haemophiliacs 44 out of 103 joints showed US score ≤5, and 59 US score >5. Joints with US score ≤ 5 had a low PXS (SRCC=0.375, P < 0.01) and joints with US score > 5 showed a high PXS (SRCC=0.440, P<0, 01). A significant correlation between US score and PXS for bone remodelling [Spearman's rho Correlation Coefficient (SRCC)] =0.429 p<0, 01 and for osteophytes (SRCC= 0.308 p<0, 05) was found. The correlation between the US score and number of bleedings in 103 joints was very significant (SRCC=0.375, P < 0.01). A total of 34 bleeding joints were identified and verified with aspiration of haematic fluid. Conclusions: US may detect bone and cartilage alterations and synovitis. Indeed PDUS identified bleeding also in asymptomatic joints and was able to show different entity of haemarthrosis. US may be a feasible and reliable tool to evaluate joint modifications in HA. Disclosure of Interest: None Declared